1964
DOI: 10.1126/science.144.3620.839
|View full text |Cite
|
Sign up to set email alerts
|

Large Electron Pulses in Hydrocarbons

Abstract: When gamma rays pass through purified, degassed, liquid hydrocarbons held in an electric field, large current pulses are observed, indicating electron multiplication. This seems to indicate that free electrons are stable in these liquids and that their mean free paths may be much greater than had been thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
1971
1971

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Samuel et al (86) have observed large pulses of current from conductiv ity cells filled with hydrocarbon and subjected to'Y rays (with applied field strengths of the order of thousands of volts per em). The current per pulse was about 104 times larger than could be accounted for by any reasonable ion yield.…”
Section: Ions and Ionic Reactionsmentioning
confidence: 99%
“…Samuel et al (86) have observed large pulses of current from conductiv ity cells filled with hydrocarbon and subjected to'Y rays (with applied field strengths of the order of thousands of volts per em). The current per pulse was about 104 times larger than could be accounted for by any reasonable ion yield.…”
Section: Ions and Ionic Reactionsmentioning
confidence: 99%